2008
DOI: 10.1016/j.ejvs.2008.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Results of Subintimal Angioplasty and Percutaneous Transluminal Angioplasty in Superficial Femoral Artery Occlusions

Abstract: Results from subintimal angioplasty of superficial femoral artery occlusions was superior to the results of PTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…Another study by Boufi et al 6 demonstrated that combining SA with a stent-graft along the entire subintimal tract did not improve patency when compared to not receiving a stent. [5][6][7][8][9][10]14 Furthermore, our outcomes were superior compared with the data from Antusevas et al 9 As we reported, we routinely implanted a stent at the proximal stump to keep the entry into the subintimal channel open, and we tried not to cover long lesions with multiple stents because we wanted to avoid stent fractures or difficulties during future bypass surgery. [7][8][9][10]14 In the present study, the 1 and 3 years rates for freedom from restenosis (77% and 59%, respectively) were comparable to previous studies.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Another study by Boufi et al 6 demonstrated that combining SA with a stent-graft along the entire subintimal tract did not improve patency when compared to not receiving a stent. [5][6][7][8][9][10]14 Furthermore, our outcomes were superior compared with the data from Antusevas et al 9 As we reported, we routinely implanted a stent at the proximal stump to keep the entry into the subintimal channel open, and we tried not to cover long lesions with multiple stents because we wanted to avoid stent fractures or difficulties during future bypass surgery. [7][8][9][10]14 In the present study, the 1 and 3 years rates for freedom from restenosis (77% and 59%, respectively) were comparable to previous studies.…”
Section: Discussionmentioning
confidence: 62%
“…[5][6][7][8][9][10]12 Treiman et al 5 reported that routine stenting of the entire length of the lesion after SA resulted in primary patency as low as 18% after 3 years, even though the primary patency rates were as high as 85% and 64% at 1 and 2 years. [7][8][9][10]14 In the present study, the 1 and 3 years rates for freedom from restenosis (77% and 59%, respectively) were comparable to previous studies. The primary patencŷT rates of bailout stenting at 1 and 2 years ranged from 55% to 97% and 42% and 94%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 24) Other comparative studies found no difference in the technical success rates for the 2 strategies. 21) 22) 24) However, Soga et al 22) reported that 25% of the IA cases in their study crossed over to a subintimal approach due to technical difficulties during IA. SA also had a significantly shorter procedure time, lesser use of guidewires, body surface echography, and IVUS.…”
Section: Technical Successmentioning
confidence: 91%
“…However, as operators accumulated experience and adopted retrograde approaches from distal arteries and using re-entry devices, the technical success rate gradually improved ( Tables 1 and 2 ). 6) 7) 8) 9) 10) 11) 12) 13) 14) 15) 16) 17) 18) 19) 20) 21) 22) 23) 24) …”
Section: Technical Successmentioning
confidence: 99%
See 1 more Smart Citation